Production, Distribution, Use and Curation: A Study of Stamped Tile from Gloucestershire. (November 2017) - Warry, Peter
Abstract: This paper explores the development of tile-stamping in the perioda.d. 100–50 by the Gloucester and Cirencester civic authorities, and by private tile-makers in Gloucestershire, and the territorial divisions between them. It argues that builders' merchants were used in tile distribution and building reclamation and, inter alia, identifies Hucclecote villa as such a site. It proposes that Gloucester tiles stamped just RPG were issued annually and were used for commercial purposes while tiles with magistrates' names were issued as required, but only for use on public buildings. The evidence suggests that these stamps were subsequently extensively curated. This paper adds nearly 200 new stamps to the existing catalogues and proposes significant revisions to the magistrate dies as a result.